The Evaluation of production, consumption and nutritive value of gurasa, an Indigenious Flat Bread of North-Western Nigeria - Agbara, Gervase Ikechukwu; Barde, Aminu; Ali, Halima Sadiya; Adams, Fannah Mustapha (International Journal of Scientific Research and Management (IJSRM), 2018)
AbstractA survey was conducted using structured questionnaire to evaluate the production and consumption pattern of gurasa,an indigenious flat bread consumed in northwestern Nigerian comprising of seven States. Also nutritive value of randomly selected gurasa samples were analyzed. Ninety eight percentage (98%) sampled consume this productany time of the day (52%) and few others for breakfast(27%), usually accompanied with yaji(spiced defatted peanut powder)(54%). More producers were males (25.7%), more consumers (32%) females mainly in the age group of 21-31. Kano, Katsina, Kaduna, Jigawa  harbour 74.3% of producers and 79% of consumers. Keep quality was less than five days (60%), less three days (40%), therefore improvement in keeping quality (41%), (37%) solicited. Yong adults were the producers who obtained the skill from parents/relatives (91%), those with less than five years were 40.5% and 6-11 years of experience, 43.3%. Local oven fueled by corn stalk were involved in baking 81% and 75.7% respectively. Need for expansion called for assistance in the area of working capital (56.75) and provision of storage facility (36.72%) to further improve profitability through greater turnover. Moisture, protein, fat, ash, dietary fiber and carbohydrate of sampled gurasa varied significantly from 28.09-30.11%, 8.96-11.68%, 4.03-5.00, 1.79-3.11%, 0.92-1, 12% and 50.00-55.04%. Weight, volume and specific loaf volume varied significantly from 108.34-119.27g, 211.96-260.17ml and 1.93-2.22ml/g respectively. It is suggested that government intervention is necessary to modernize, harmonize and regulate this subsector that help to eliminate food insecurity. Nutritional quality could be improved by partial substitution of the refined wheat flour with pulse flour since majority could not afford animal protein.Key words: Flat bread, Gurasa, Nutritive value, Production survey, Consumption survey.